Working Qualities of Indian Timbers-Part VIII - Pant, B. C.; Shukla, K. S.; Badoni, S. P. (Indian Forester, 1989)
Briefly reviewing the work done so far on the evaluation of wood working qualities of Indian timbers the results of study done on six more species namely- Acer oblongum, Cupressus torulosa, Dalbergia sericea, Daphniphyllum himalayense, Olea glandulifera and Quercus serrata are presented. The working quality index based on quality of worked surface and ease of working of these species are reported along with teak, tested earlier. for comparison. The results of this study indicate that all the species can be worked to acceptable smooth surface easily.